2,4-Di-tert-butylphenol from Endophytic Fungi Fusarium oxysporum attenuates the growth of multidrug-resistant pathogens - Ranjitha Dhevi V. Sundar; Sathiavelu Arunachalam (Frontiers in Microbiology)
IntroductionThe continuous emergence of drug-resistant pathogenic bacteria highlights the persistent importance of discovering and developing new antibiotics. Endophytic species are an infinite source of several medicinally essential secondary metabolites.MethodsThe current study focuses on isolating secondary metabolites from the endophytic Fusarium oxysporum TPL11 fungus of Tradescantia pallida plant. These fungi were spectrally analyzed by nuclear magnetic resonance (NMR), Fourier transform infrared spectroscopy (FTIR), gas chromatography-mass spectrometry (GC-MS), and the structures were predicted. The pure compounds were tested for antagonistic susceptibility to multidrug-resistant (MDR) pathogens using disk diffusion, minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC), time-kill kinetics, and cytotoxicity assays.Results and discussionBioactivity-guided extraction of ethyl acetate fungal extract purification yielded a lead compound, 2,4-di-tert-butylphenol (DTB), which was interpreted by combining 1H NMR, 13C NMR, and mass spectrometry (MS) data. The compound DTB displayed antagonism against human pathogens with diameters ranging from 16 to 26 mm. The highest antagonistic effect was against methicillin-resistant Staphylococcus aureus (MRSA) (ATCC 700699) and VRE (ATCC 51299) with 21 ± 0.2 and 22 ± 0.5 mm zones of inhibition, respectively. The compound had MICs of 3.12 and 6.25 μg/mL, and MBCs of 0.78 and 3.12 μg/mL against MRSA (ATCC 700699) and vancomycin-resistant Enterococcus faecalis (VRE) (ATCC 51299), respectively. The time-kill kinetics study reveals that DTB displayed a bactericidal effect against pathogens at higher concentrations, indicating a concentration and time-dependent interaction. In a cytotoxicity assay, it is more active against the cell line with a decrease in cell viability of 50.12% at 1,000 μg/mL concentration. The results highlighted that compound DTB from F. oxysporum showed significant pharmaceutical potential, indicating its suitability as a lead molecule. The study outcome suggests that the active lead metabolites isolated for the first time from F. oxysporum isolated from T. pallida plant can be an auspicious antibacterial agent for controlling multidrug-resistant pathogens marking a novel discovery in this domain.